Comparing Mindful and Non-Mindful Exercises on Alleviating Anxiety Symptoms: A Systematic Review and Meta-Analysis - So, Wendy Wing Yan (Int J Environ Res Public Health, 2020)
Background: In recent years, studies and reviews have reported the therapeutic benefits of both mindful and non-mindful exercises in reducing anxiety. However, there have not been any systematic reviews to compare their relative effectiveness for therapeutic application, especially among the non-clinical population. Thus, the aim of this review is to compare the effectiveness between mindful and non-mindful exercise on treating anxiety among non-clinical samples. Methods: Potential articles were retrieved from PubMed, Embase, Academic Search Premier, and PsycInfo. Randomized controlled trials, which involved both mindful and non-mindful exercises as intervention, and the use of anxiety outcome measures were included. Results: Twenty-four studies fulfilled the inclusion criteria and were included in our systematic review. In addition, 14 studies provided sufficient data to be included in the meta-analysis. For studies that reported significant group differences at post-assessment, results showed that mindful exercise was more beneficial in reducing anxiety than non-mindful exercise. The meta-analysis reported that yoga was more effective in reducing anxiety than non-mindful exercise. Conclusions: Compared to non-mindful exercise, yoga is shown to be more effective in alleviating anxiety symptoms. It is recommended that yoga could be used as a primary healthcare intervention to help the public reduce anxiety.